PENERAPAN MODEL THINK TALK WRITE (TTW) UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI SISWA KELAS IV SD NEGERI 6 GANDAPURA KABUPATEN BIREUEN - Sri Rezeki Agustinur; Intan Safiah; Hasniyati (STKIP Subang, 2026)
This study was motivated by the low poetry writing skills of fourth-grade students at SD Negeri 6 Gandapura in Bireuen Regency regarding contemporary poetry, as well as the students’ suboptimal engagement in the learning process. The study aimed to enhance students’ learning activities and poetry writing skills through the Think Talk Write (TTW) model. This study was a Classroom Action Research (CAR) project conducted over two cycles. The research subjects consisted of 23 fourth-grade students at SD Negeri 6 Gandapura, Bireuen Regency, for the 2025/2026 academic year. Data were collected through observations of teacher and student activities as well as poetry writing skill tests. The data were analyzed using descriptive qualitative and quantitative methods. The results showed that teacher activity increased from 87.5% in Cycle I to 97.91% in Cycle II, falling into the “very good” category. Student activity increased from 72.72% to 90.90%, also falling into the “very good” category. The class-wide mastery of poetry writing skills also increased from 56.52% in Cycle I to 82.61% in Cycle II. Based on these findings, the implementation of the Think Talk Write (TTW) model can improve learning activities and contemporary poetry writing skills among fourth-grade students at SD Negeri 6 Gandapura, Bireuen Regency.